Djibouti, 1: 10 000 plan guide - Institut geographique national (France) (Paris : L'Institut, 1985)
Includes indexes and 2 insets: location map and Les iles.
Photomap.
Panel title.
Includes indexes and 2 insets.
Keywords: Djibouti (Djibouti) -- Photo maps